Kecelakaan Kerja pada Perawat di Rumah Sakit Universitas Hasanuddin Makassar - Novriani Zainuddin; Yahya Thamrin; Ikhram Hardi; Haeruddin Haeruddin; Alfina Baharuddin; Yuliati Yuliati (Lontara Journal of Health Science and Technology, 2024)
A work accident is an event that is detrimental to humans and the production process, and permanent disability or even death caused by a work process. The cause of the accident consists of two factors, namely human factors, and environmental factors. Hospitals are required to implement occupational health and safety efforts that are carried out in an integrated, comprehensive manner. This research was conducted with the aim of To find out factors related to work accidents among nurses at Hasanuddin University Hospital, Makassar. This research uses quantitative research, with analytical observational methods and a cross-sectional study design. The research population was 213 nurses at Hasanuddin University Hospital, Makassar. The research sample of 100 nurses on duty at Hasanuddin University Hospital in Makassar was taken using the sampling method in this study using probability sampling with simple random sampling. Research data was analyzed using a logistic regression test on 95% PPE use (a=0.05). The results of this study show that there is a significant influence between the variables K3 knowledge, K3 training (a=0.040), and work attitude (a=0.017), use of PPE (a=0.033), on work accidents, while the variables gender, length of service and work environment do not there is an influence on work accidents. Apart from that, the most influential variable is the use of PPE on work accidents with Standardized Coefficients Beta 3.252. It is hoped to improve occupational health and safety in hospitals so that the number of work accidents does not occur among nurses and staff in the hospital environment and can improve the quality of hospitals as expected.